To determine the total change to John's account after his two transactions, we need to consider that withdrawing money (using the debit card) is a negative change, and writing a check (which also causes money to be taken out) is likewise a negative change.
- John withdrew $55 from the ATM, which can be represented as -$55.
- He wrote a check for $18, which is another negative change, represented as -$18.
The total change to John's account can be calculated by adding these two negative amounts:
Total Change = -55 + (-18) = -55 - 18 = -73
Thus, the equation that represents this total change to John's account is:
-55 + (-18) = -73
So, the correct response is: −55 + (−18) = −73